Aging temperature effect on the phase composition, microstructure, and selected mechanical properties of non-equiatomic TiZrNbTaMo/Mn HEAs targeted for biomedical implants - Torrento, Jhuliene Elen Muro [UNESP]; dos Santos Pereira de Sousa, Tiago [UNESP]; da Cruz, Nilson Cristino [UNESP]; Afonso, Conrado Ramos Moreira; Grandini, Carlos Roberto [UNESP]; Correa, Diego Rafael Nespeque [UNESP] (Elsevier, 2024)
High entropy alloys (HEAs) have been developed for many applications and recognized for their superior strength, ductility, and corrosion resistance, attracting the attention for biomedical applications. This study aims to evaluate the effect of aging treatment at distinct temperatures on the phase composition, microstructure, and selected mechanical properties of non-equiatomic TiZrNbTaMo and TiZrMoNbTaMn HEAs for potential use as biomedical implants. The TiZrNbTaMn sample exhibited a single BCC phase, while the TiZrNbTaMo a major BCC and minor HCP phases. The microstructure of the TiZrNbTaMo sample was composed of BCC grains with some acicular precipitations of the HCP phase in the grain boundaries, having the aging temperature acted in the grain growth and secondary phase precipitation. Contrarily, the TiZrNbTaMn sample exhibited larger BCC grains permeated with a minor amount of acicular structures, which were entirely decomposed with the aging treatments. The semi-quantitative chemical analysis indicated that the phase composition was a result of elemental chemical segregation, having the refractory metals (Mo, Ta, and Nb) preferentially located in the inner region of the grains, while the other ones (Ti, Zr, and Mn) in the grain boundary. The aging treatment acted in the phase precipitation/dissolution oppositely on the samples through the atomic diffusion mechanism induced by the temperature. The elastic modulus and Vickers microhardness were sensitive to the chemical and phase composition of the samples, having the TiZrNbTaMo aged at 773 K achieved better performance than the commercial Ti-6Al-4 V alloy for use as biomedical implants.
Keywords: Aging; High entropy alloys; Mechanical properties; Metallic biomaterials; Microstructure; Phase composition